A simplified method of measuring thermal conductivity of β-Ga2O3 nanomembrane. (27th October 2020) - Zheng, Yixiong; Seo, Jung-Hun
Abstract: In this work, we report a simplified method to measure thermal conductivity from the typical Raman thermometry method by employing a much simpler dispersion relationship equation and the Debye function, instead of solving the heat equation. Unlike the typical Raman thermometry method, our new method only requires monitoring of the temperature-dependent Raman mode shifting without considering laser power-dependent Raman mode shifting. Thus, this new calculation method offers a simpler way to calculate the thermal conductivity of materials with great precision. As a model system, the β -Ga2 O3 nanomembrane (NM) on a diamond substrate was prepared to measure thermal conductivity of β -Ga2 O3 NMs at different thicknesses (100 nm, 1000 nm, and 4000 nm). Furthermore, the phonon penetration depth was investigated to understand how deep phonons can be dispersed in the sample so as to guide the dimensional design parameter of the device from the thermal management perspective.